Analisis Potensi Pengembangan Ekowisata Mangrove di Desa Maitara Tengah Kota Tidore Kepulauan - Novlandi Maradjabessy; Nuraini Adung Damsiki; Muhammad Ali Ahmad (Peneliti.net, 2023)
This study aims to calculate the thickness and density of mangrove ecosystems in the waters of Maitara Tengah City of Tidore Islands and calculate the suitability of mangrove ecosystems for ecotourism in the waters of Maitara Tengah Village while the use of research is as reference material for further research activities as well as a basis for consideration in management of mangrove ecotourism areas using the concept of conservation for related agencies. The results of data collection at the two observation stations using the